A physical development plan for the Tygerberg Hills area - Boshoff, Jacobus Johannes Christoffel (School of Architecture, Planning and Geomatics, 2020)
It has been aptly said that one thing in the world is invincible .... an idea whose time has come. Such an idea in our days, I believe, is the care of man's ancestral home .... the natural environment. However, our country is still in a pioneering stage in so far as it, up till now, accepts the rugged principle that man has the freedom to do with his land just about whatever he wants to do. Under a proud banner of the above “right”, man is unscrupulously exploiting his natural resources and ruthlessly despoiling his landscape. This really boils down to uncontrolled speculation and limitless profit to the few in the name of progress and, if this is how the development of the environment is understood by man, then the perfect formula has already been found. That is to say, that no planning is needed .... planning is then obviously only an obstacle in the free- for-all, laissez-faire competitive market.